PENGARUH PENAMBAHAN TEPUNG KECOMBRANG (Etlingera eliator) DAN LAMAPENYIMPANAN SUHU DINGIN TERHADAP KUALITAS MIKROBIOLOGI BAKSO AYAM - Dyah Nurul Afiyah; Asrorul Muhimah (Universitas Islam Kadiri, 2017)
The aims of this reseach was to know the influence of kecombrang flour addition and long cold refrigerator on microbiological quality chicken meatball. Variables in the study include : Total Plate Count and Figures Fungus / Yeast. The research method used was experimental using Factorial Random Design Randomized Design (RAL). There is a significant difference then it is continued with Duncan's multiplexed test of 5%.mThe results showed that the average number of ALT in chicken meatball the smallest was the (5,97) and the highest (6,31), while the average figures Fungus / Yeast in chiken meatball the smallest was the (0,00), and the highest (2,75). The amount of ALT during the lowest storage is (5,64), and the highest (6,73), while the figures Fungus / Yeast during the lowest storage is (0,25), and the highest (2,42). The figures of ALT in the lowest combination is (5,19), and the highest (6,74), while the figures Fungus / Yeast in the lowest combination is (0,00), and the highest (5,58). Based on the research result, it can be concluded that of kecombrang flour addition and long cold refrigerator on microbiological quality chicken meatball very significant effect on the amount of ALT and Kapang Khamir in chicken meatball during storage. The treatment of kecombrang flour addition a significant effect on the amount of ALT in chicken meatball, and very significant effect on figures Fungus / Yeast in chicken meatball. While the combination of treatment gave a real effect on the amount of ALT and very significant effect on figures Fungus / Yeast in chicken meatball